Synthesis, characterisation and qualification of high performance phenolic/carbon random-fibre oriented ablative thermal protection composite for re-entry applications. (29th December 2021) - Kumar, L. Mohan; Chakravarthy, P.; Anandapadmanabhan, E.N.
Ablatives are an elite class of fibre-reinforced polymer composites, which find wide applications in re-entry space vehicles, solid rocket motor nozzles, liquid engine throats, control thrusters, etc. They are synthesised from a high temperature-resistant fibre-like carbon or Silica and a high char-yielding polymeric resin like phenolics. This paper describes a novel method to synthesise a near net shape carbon phenolic ablative composite for re-entry applications through consolidating prepreg of 15 mm × 15 mm in a pre-designed mould. Subsequently, the random fibre-oriented composite laminates were subjected to various characterisation techniques and mechanical testing to qualify the same for re-entry missions. Thermal performance was evaluated under simulated re-entry conditions in a plasma wind tunnel. Property comparison and validation of performance in subscale tests are also discussed for random fibre-oriented composite and the layered laminate composite made through stacking plies one over the other. It was observed that the random fibre-oriented carbon phenolics composite possessed superior properties and exhibited better performance the layered laminate composite for re-entry and other space mission applications.